(untitled) (Research, Society and Development, 2021)
Interdisciplinarity in high school is still scarce and the understanding of the relationship between the environment and human beings is still distant. This research aimed to verify the existence of obstacles to interdisciplinarity between Biology Teaching, Ethnobotany and Environmental Education in the third year of High School. The method applied was deductive, associated with Evidence-Based Investigation (EBRI) and Zipf’s Law. The data obtained and analyzed indicated that of the 189 preselected literatures, in three academic bases: CAPES Periodical Portal, Google Scholar and SciELO, only a small portion of them (n = 45.0; 23.8%), presented at least one of the 10 selective descriptors associated, whose highest frequency fell to the one identified as 2.2 (6.2±8.4). Thus, the scarcity of studies that integrate the investigated triad was verified; however, there were indications of potential explorers to be employed on the theme, with the purpose of forming greater environmental awareness through the biology discipline in high school.